RELATIONSHIP BETWEEN SCROTAL CIRCUMFERENCE OF NELLORE BULLS AND COW PREGNANCY RATE IN NATURAL MATING - Oliveira Junior, D. R.; Dias, E. A. R.; Campanholi, S. P. [UNESP]; Monteiro, F. M.; Paz, C. C. P.; Mercadante, M. E. Z. (Inst Zootecnia, 2016)
The pregnancy rate is extremely important for the productive efficiency of beef cattle and bull fertility can influence the pregnancy rate of cows in natural mating. The objective of this study was to evaluate the relationship of andrological traits, especially scrotal circumference (SC), of Nellore bulls (Bos indicus) selected for breeding based on greater postweaning weight gain with the pregnancy rate of naturally mated Nellore cows in a 90- day breeding season. Records of 7,171 entries into the breeding season of 1,923 cows exposed to 216 bulls in 368 mating batches in the field (single bull) from 1995 to 2014, as well as records of SC, were evaluated. Scrotal circumference was pre- adjusted for bull age (2.67 +/- 0.62 years) at the start of the breeding season using a linear regression model and was divided into three classes: class 1: SC < 35 cm; class 2: 35 >= SC < 37 cm; class 3: SC >= 37. More than half the observations of SC were in class 2 and 74.52% of the exposures to bulls resulted in pregnancy, with a minimum rate of successful pregnancy of 0% and a maximum rate of 100% in the 368 mating batches. Thirty-three of the 216 bulls had records of andrological traits [SC, sperm volume, motility, vigor, concentration and morphology (major and minor defects)]. The class of intermediate SC values (class 2: 35 >= SC < 37 cm) was associated with a higher relative risk of pregnancy success. In the sample of the 33 bulls, pregnancy rate showed a moderate positive correlation (r = 0.66) only with sperm concentration. The weak association between andrological traits of bulls and pregnancy rate might be due to the fact that the sample of bulls evaluated in this type of study will be always biased. In other words, only bulls that enter the breeding season are considered, which correspond to a small percentage of all males born. Consequently, the variation observed in these bulls does not represent the variation in SC, seminal traits and, possibly, reproductive fitness of all bulls born. In addition, pregnancy rate is the result of the expression of many factors that affect cows and bulls differently and that are likely to have a subtle individual influence on this outcome.
Keywords: Bos indicus; scrotal circumference; pregnancy; semen